(untitled) (Global Scientific Review, 2023)
This research aims to analyze the development of visual arts and crafts based on local wisdom in learning at the Visual Arts Study Program, Gorontalo State University . The research method used is descriptive qualitative to identify, observe and analyze field conditions in the local wisdom-based learning process carried out. The data analyzed is data on the learning process of visual arts and crafts based on local wisdom observed in the textile arts and crafts course. The aspects observed are lecturer activities in managing learning, and student activities as learning participants, student response data and learning result data from learning participants. The research results show that the observation indicators show varying results. The results of data analysis on the ability of lecturers’ activities in managing learning about Karawo Textile Arts based on local wisdom reached the criteria of quite good 21%, good 26% and very good 53%. Meanwhile, the results of the analysis of learning participants’ activities also show that the percentage of learning participants’ activities for each aspect observed in the implementation of learning is within the criteria for ideal tolerance limits which are determined by two aspects and the criteria below, while those who get tolerance limits below ideal have three aspects. Thus, it can be concluded that there are still shortcomings in the implementation of the development of visual arts and crafts based on local wisdom in learning can be improved by creating teaching materials based on local wisdom and innovative learning media in order to provide a better learning experience for students.